Smoking in pregnancy: who makes quit attempts whilst pregnant and what types of cessation support do they prefer? - Brotherton, Emma; Orton, Sophie; Coleman, Tim (2016)
Background Smoking in pregnancy is strongly associated with adverse pregnancy and birth outcomes. In England, 26% of women smoke at some point during pregnancy, and 12% smoke throughout. Reducing smoking during pregnancy is therefore an NHS priority. Despite this, little is known about women who make a quit attempt during pregnancy. This study examined sociodemographic and psychological characteristics associated with making a quit attempt during pregnancy, and explored preferences for cessation support.